Genetic Screening of Deficiency of Uridine Monophosphate Synthase (Dumps), Bovine Citrullinaemia (BC) and Factor Xi Deficiency (Fxid) in Hardhenu, Sahiwal and Hariana Bulls - Magotra, Ankit; Patil, C. S.; Malik, B. S.; Garg, Asha Rani (International Journal of Bio-resource and Stress Management, 2020)
Genetic disorder is an inborn genetic abnormalities in animals that is due to mutation in genes which are quite rare and recessive in nature. Propagation of mutated alleles constitute a danger whose negative effect often become evident only after several generations of breeding. Most commonly reported genetic diseases like Deficiency of uridine monophosphate synthase (DUMPS), bovine citrullinaemia (BC) and factor XI deficiency (FXID) affecting significantly on economics of dairy farming.The present study involved screening of 50 animals viz. Hardhenu (n=25) Sahiwal (n=15) and Hariana (n=10) cattle for autosomal recessive genetic disorders such as Deficiency of Uridine Monophosphate Synthase (DUMPS), Bovine Citrullinemia (BC) and Factor XI Deficiency (FXID) using PCR based techniques. Blood samples were collected from the jugular vein into EDTA containing tubes and stored at -20 °C until genomic DNA extraction, which was carried out using Phenol Chloroform method. PCR-RFLP and allele specific PCR was used for screening. The amplified PCR products were digested with AvaI and AvaII restriction enzymes for DUMPS and BC respectively. Animals were screened for FXID based on PCR conformation.All the animals under study were found to be free from DUMPS, BC and FXID as the amplified PCR products upon RE digestion revealed fragments for normal animals. The genetic screening revealed that none of the animal screened under study was carrier for any genetic disorder.